Correlation of Modified Computed Tomography Severity Index with Biochemical Markers in Acute Pancreatitis - Joshi BR; Kumar S; Khanal UP (Journal of Radiation and Nuclear Medicine, 2021)
Introduction Multislice computed tomography examinations performed 3 to 4 days after the onset of symptoms is the imaging procedure of choice in acute pancreatitis, which is mainly done for evaluating the complications. Due to radiation exposure and cost, alternative scoring systems like Ranson’s score and Glasgow’s score were devised but were cumbersome. The serum amylase and lipase were found to increase with progression of disease. The objective of this study was to evaluate the association of acute pancreatitis by modified CT scoring system with the serum levels of amylase and lipase. Material and Methods In hundred patients presenting with acute pancreatitis, the severity of pancreatitis was recorded using the modified CT severity index. The serum amylase and lipase levels were recorded and correlated with modified CT severity index score. Results Among 100 patients studied, 46%, 40% and 14% had mild, moderate and severe grades of pancreatitis respectively by modified CTSI score. No significant correlation was found between the levels of serum amylase (r = -0.104, p = 0.301) and lipase (r = -0.177, p = 0.079) with the modified CT severity index in patients with acute pancreatitis. Conclusion The serum level of amylase and lipase had non-significant correlation with the modified CT severity index score and thus did not indicate severity of pancreatitis.
Keywords: Acute pancreatitis